Effects of cilostazol, a Phosphodiesterase-3 inhibitor, on kidney function and redox imbalance in acute kidney injury caused by Bothrops alternatus venom - Marinho, Aline Diogo; Coelho Jorge, Antônio Rafael; Nogueira Junior, Francisco Assis; Alison de Moraes Silveira, João; Rocha, Danilo Galvão; Negreiros Nunes Alves, Ana Paula; Ferreira, Rui Seabra [UNESP]; Bezerra Jorge, Roberta Jeane; Azul Monteiro, Helena Serra (Elsevier, 2022)
The mechanisms of pathogenesis of acute kidney injury (AKI) in snakebites is multifactorial and involves hemodynamic disturbances, with release of free radical causing cytotoxic effects. The phosphodiesterase-3 (PDE3) inhibitor, Cilostazol, has been reported to provide protection against renal oxidative stress. Objective: We evaluated the protective effects of cilostazol against Bothrops alternatus snake venom (BaV)-induced nephrotoxicity. Methods: Wistar rat kidneys (n = 6, 260–300 g) were isolated and perfused with Krebs-Henseleit solution containing 6 g/100 mL of bovine serum albumin. After 30 min, the kidneys were perfused with BaV to a final concentration of 1 and 3 μg/mL, and subsequently evaluated for perfusion pressure (PP), renal vascular resistance (RVR), urinary flow (UF), glomerular filtration rate (GFR), and percentage of electrolyte tubular sodium and chloride transport (%TNa+, %TCl–). Oxidative stress and renal histological analyses were performed. Results: BaV caused a reduction in all the evaluated renal parameters (PP, RVR, GFR, UF, %TNa+, and %TCl–). Although only the effects on PP and UF were reversed with cilostazol treatment, the decrease in the malondialdehyde levels, without changes in glutathione levels, further reduced the venom-induced renal tissue changes. Conclusion: Our data suggest that PDE3 is involved in BaV-induced nephrotoxicity, as cilostazol administration significantly ameliorated these effects.
Keywords: Bothrops alternatus; Kidney injury; Kidney perfusion; Phosphodiesterase-3 inhibitor; Snake envenomation